2017
DOI: 10.1039/c6sc01829g
|View full text |Cite
|
Sign up to set email alerts
|

Protecting microRNAs from RNase degradation with steric DNA nanostructures

Abstract: A DNA nanostructure bearing a “Shuriken” shape is designed to deliver, protect and activate microRNA-145 functionality in human colorectal cancer cells. This novel DNA nanostructure enabled therapeutic platform greatly suppresses cancer cell proliferation and tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…DNA strands can be modified with cellular recognition signals, such as folate, transferrin, or aptamers, which permit the assembly of functionalized DNA-based nanostructures (DNS) useful for selective targeting into cells through receptor-mediated mechanism [3][4][5]. Due to their intrinsic biocompatible, nontoxic, and stable properties, DNS have been extensively investigated for various biomedical applications, such as drug delivery, cellular biosensing, and in vivo imaging [4][5][6][7][8], and, more recently, in gene silencing and RNA anticancer therapy [9,10]. Different shape-changing structural modules can be integrated in the DNS, allowing input-induced conformational changes.…”
Section: Introductionmentioning
confidence: 99%
“…DNA strands can be modified with cellular recognition signals, such as folate, transferrin, or aptamers, which permit the assembly of functionalized DNA-based nanostructures (DNS) useful for selective targeting into cells through receptor-mediated mechanism [3][4][5]. Due to their intrinsic biocompatible, nontoxic, and stable properties, DNS have been extensively investigated for various biomedical applications, such as drug delivery, cellular biosensing, and in vivo imaging [4][5][6][7][8], and, more recently, in gene silencing and RNA anticancer therapy [9,10]. Different shape-changing structural modules can be integrated in the DNS, allowing input-induced conformational changes.…”
Section: Introductionmentioning
confidence: 99%
“…So these DNA motifs have been used to trigger host immune response as these are recognized by TLR-9 located on endosomes of host membrane of immune system which activates the innate immune pathway of host immune system. Similarly, siRNA and miRNA delivery have also been carried out using DNA nanostructures for gene silencing applications (Lee et al, 2012;Fakhoury et al, 2013;Bujold et al, 2016;Roh et al, 2016;Qian et al, 2017;Nahar et al, 2018). Various types of DNA nanostructures, that have been used as delivery vehicles, are listed in Table 4 (Hu et al, 2018;Madhanagopal et al, 2018).…”
Section: Dna Nanotechnology-based Drug Deliverymentioning
confidence: 99%
“…Nevertheless, their biomedical application is still in its infancy. Due to the nature of DNA, this new class of material is sensibly considered a potential smart material platform as drug delivery vehicles, sensors and other functional units . Thus far, self‐assembled DNA nanostructures have been successfully explored as drug delivery vehicles for small molecule drugs, siRNA, proteins and other guest molecules in vitro or in vivo.…”
Section: Figurementioning
confidence: 99%
“…Numerous studies have revealed that DNA nanostructures showed certain stabilities compared with single‐stranded or duplex nucleic acid under physiological conditions . It was believed that the stability of DNA nanostructures is attributed to the steric effect and highly associated with the structural design. In the present study, we also evaluated the thermal and physiological stabilities of DNA nanoprism with PAGE.…”
Section: Figurementioning
confidence: 99%